2021
DOI: 10.1021/acscatal.1c02083
|View full text |Cite
|
Sign up to set email alerts
|

Developing Efficient Suzuki Cross-Coupling Catalysts by Doping Palladium Clusters with Silver

Abstract: It is shown that doping of a Pd cluster by Ag atoms can provide an efficient catalyst for the Suzuki–Miyaura cross-coupling reactions. We demonstrate this intriguing possibility by considering a model reaction involving bromobenzene and phenylboronic acid as reagents where the reaction involves oxidation, transmetallation, and reduction steps. We have examined the reaction barriers of all three steps for a conventional ligated Pd catalyst, a nearly icosahedral Pd13 cluster, and a monosilver-doped Pd12Ag cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…So, we speculate that besides the roles of Cl − ion mentioned above, a suitable amount of chloride ion may be also helpful for reducing the reaction barrier on the oxidative addition. 50 This is still a question to be searched in the future.…”
Section: Resultsmentioning
confidence: 99%
“…So, we speculate that besides the roles of Cl − ion mentioned above, a suitable amount of chloride ion may be also helpful for reducing the reaction barrier on the oxidative addition. 50 This is still a question to be searched in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this fact can be also confirmed by the average local ionization energy (ALIE) plot as shown in figure S4. It is observed that the local minima (marked with blue dots) of ALIE are always distributed on the O, S, and N atoms of drug molecules, further indicating that these sites are more susceptible to the electrophilic attack [50].…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…In order to understand the in-depth nature of the oxidative addition of PhBr onto Al 12 M, the NPA charges on the Al 12 M units in the 1 M and 2 M * structures are illustrated in Figure S7. According to molecular orbital theory, 16,60 the electron pair from the bonding orbital of the C−Br bond is first donated to the empty hybrid orbital of metal atoms on the surface of Al 12 M, resulting in the negative charges on the Al 12 M units in 1 M during the initial adsorption of PhBr onto Al 12 M (see Figure S7). For Al 12 C and Al 12 P with 40 and 41 valence electrons, respectively, the acquisition of extra electrons from PhBr is detrimental to their stability in the resulting 1 M complexes, which leads to the higher relative free energies (ΔG) of 1 C and 1 P than those of 1 Be and 1 Al (see Figure 5).…”
Section: Oxidative Additionmentioning
confidence: 99%